Feminization of employment in the Turkish banking sector: A critical analysis - Muhtar, Gizem Melis. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
This thesis analyzes the feminization trend in the Turkish banking sector with a critical perspective. The aim of the study is twofold. The first part lays down the factors that contribute to the feminization of the sector and their implications for women’s representation in the horizontal and vertical occupations. The second part investigates the impact of economic crises that Turkey has gone through in 1994, in 2000-2001, and in 2008 on this feminization process. The thesis utilizes a multilevel framework which takes gender to the center of its analysis. This framework includes both qualitative and quantitative methods. Data on banking sector employees by sex and education level is used together with the literature on occupational segregation in order to elicit women’s horizontal and vertical representation. Econometric tools are also used to bring out the effects of economic crises on women’s employment in the Turkish banking sector. Additionally, semi-structured interviews are conducted with the human resources managers of sample banks to present the personal, organizational, and cultural attitudes towards female employment in the sector. The first set of findings suggest that although equality in the number of employees from each gender is achieved in the sector, such equality does not correspond to an equal representation of the genders in terms of horizontal and vertical occupational categories. The second set of findings show that the feminization trend was broken in 1994 and 2000-2001 crises, and returned back to its course when the crises were over indicating that the pattern of female employment changed during these crises. However, 2008 crisis did not show the same effect on the trend.
Keywords: Women bank employees -- Turkey.; Women -- Employment -- Turkey.